Judicial Reasoning In Marriage Dispensation Cases: A Maqasid Al-Shariah Analysis Of Premarital Pregnancy - Muniroh Chamim; Zaidi Abdad; Masnun Tahir; Naura Sania Zaimi (INJECT (Interdisciplinary Journal of Communication), 2026)
Marriage dispensation requests due to premarital pregnancy have become a significant legal and ethical issue in the practice of religious courts in Indonesia. This study analyzes the judicial reasoning in Decision Number 212/Pdt.P/2023/PA.Mtr and evaluates its alignment with the objectives of Maqasid al-Sharia. This research used a case study approach to examine the court’s legal reasoning alongside relevant statutory frameworks, including Law Number 16 of 2019, Supreme Court Regulation Number 5 of 2019, and the Compilation of Islamic Law. The findings indicate that the judge relied on considerations of public benefit (maslahah) and the prevention of greater harm (mafsadah) to justify granting the dispensation. The decision frames marriage as a mechanism to protect lineage (hifz al-nasl), ensure the legal status of the unborn child, and mitigate social stigma. However, the case also reveals a normative tension between short-term social urgency and the long-term objectives of child protection within a maqasid-based framework.